Prevalence of Drooling among 5-10 Year-old Cerebral Palsy Children in Chennai: A Cross-sectional Study - Subramanian Anu Krishna Kumar; Parangimalai Diwakar Madankumar (Wolters Kluwer Medknow Publications, 2024)
Aim: The present study assessed the drooling among 5-10 year-old cerebral palsy (CP) children in a tertiary care hospital in Chennai and measured the drooling frequency and severity among them. Materials and Methods: Drooling was measured both quantitative and qualitatively. The drooling frequency score was recorded using the 5 min Drooling Quotient (DQ5) Scale. Children with CP were assessed for drooling under two different conditions (active and rest) totally for 10 min. The drooling assessment was done using the Thomas-Stonell and Greenberg classification. The severity of drooling was recorded as (1) dry - never drools, (2) mild - only lips wet, (3) moderate - wet on lips and chin, (4) severe - drools to the extent that clothing becomes damp, and (5) profuse - clothing, hands, tray, and objects become wet. The frequency of the drooling is recorded as (1) never drools, (2) occasionally drools, (3) frequently drools, and (4) constantly drools. Statistical analysis was performed using the Statistical Package for the Social Sciences (SPSS) software version. Results: A total population of 110 children were included in the study. Among the 110 patients, 82 (74.5%) were males and 28 (25.5%) were females with a mean age of 7 years ± 1 year and 9 months. The prevalence of drooling among the CP children in this study was found to be 94.5% (104 children). The average DQ score for males during rest was 55.5 and during activity was 55.87. For females, the average DQ score for males during rest was 55.5 and activity 56.18. A significant negative correlation exists between age and drooling frequency and drooling severity too. Conclusion: The present study demonstrated a significant association between drooling and age.